Biotransformation of Neoandrographolide by Endophytic Fungus from Dendrobium officinale Kimura et Migo - Wang, Jie-Hua; Wang, Zheng-Tao; Wang, Li-Li; Wang, Zhe-Jian; Ma, Zhao; Chou, Gui-Xin; Hu, Zhi-Bi; Li, Wan-Kui (Asian Journal of Chemistry, 2014)
Neoandrographolide is one of the principal constituents of ent-labdane diterpenoid lactones isolated from the aerial parts of the traditional herbal medicine Andrographis paniculata (Burm. F.) Nees. To obtain more types of diterpenoid derivatives and acquire compounds with better activities than the substrate, we used endophytic fungi to transform neoandrographolide for the first time. An endophytic fungus, namely, 2T12J01A, which was identified as Fusarium oxysporum based on 18S ribosomal DNA and the inte DNAl transcribed spacer of ribosomal DNA, was used to transform neoandrographolide and obtain four compounds: (2) isoneoandrographolide, (3) 14-deoxyandrographolide, (4) 8a,17b-epoxy-3,14-dideoxyandrographolide and (5) andrograpanin. The structural elucidation of compounds was achieved mainly by 1H- and 13C-nuclear magnetic resonance (NMR), distortionless enhancement by polarization transfer (DEPT), heteronuclear singular quantum correlation (HSQC), 1H detected heteronuclear multiple quantum coherence (HMQC), nuclear overhauser spectroscopy and high-resolution electrospray ionization mass spectrometry experiments. Finally, the proposed biosynthetic pathways of neoandrographolide by 2T12J01A were established.